Big cats in borderlands: challenges and implications for transboundary conservation of Asian leopards. Issue 3 (19th May 2021) - Farhadinia, Mohammad S.; Rostro-García, Susana; Feng, Limin; Kamler, Jan F.; Spalton, Andrew; Shevtsova, Elena; Khorozyan, Igor; Al-Duais, Mohammed; Ge, Jianping; Macdonald, David W.
Abstract: Large carnivores have extensive spatial requirements, with ranges that often span geopolitical borders. Consequently, management of transboundary populations is subject to several political jurisdictions, often with heterogeneity in conservation challenges. In continental Asia there are four threatened leopard subspecies with transboundary populations spanning 23 countries: the Persian Panthera pardus saxicolor, Indochinese P. pardus delacouri, Arabian P. pardus nimr and Amur P. pardus orientalis leopards. We reviewed the status of these subspecies and examined the challenges to, and opportunities for, their conservation. The Amur and Indochinese leopards have the majority (58–100%) of their remaining range in borderlands, and the Persian and Arabian leopards have 23–26% of their remaining ranges in borderlands. Overall, in 18 of 23 countries the majority of the remaining leopard range is in borderlands, and thus in most countries conservation of these subspecies is dependent on transboundary collaboration. However, we found only two transboundary initiatives for Asian leopards. Overall, we highlighted three key transboundary landscapes in regions that are of high importance for the survival of these subspecies. Recent listing of the leopard in the Bonn Convention on the Conservation of Migratory Species of Wild Animals is important, but more international collaboration is needed to conserve these subspecies. We provide a spatial framework with which range countries and international agencies could establish transboundary cooperation for conserving threatened leopards in Asia.